Supporting young children with communication problems - Kersner, Myra.; Wright, Jannet A. (London : Routledge, Taylor & Francis Group, 2015)
'Now in its fourth edition, this invaluable guide to understanding and helping children whose speech and/or language is delayed or impaired has been completely revised and updated, and provides readers with: - Practical advice on how to recognise communication problems - Strategies for supporting children with speech, language and communication needs - Best practice guide for parents and professionals working in partnership - Contributions from a wide-range of specialist speech and language therapists Reflecting new developments and current practice, this book is of interest to parents, early years' practitioners, students in education and speech and language therapy, and anyone interested in pursuing a career with young children in the foundation years. It assumes no prior knowledge and includes a range of practical suggestions for dealing with children with all kinds of communication difficulties'--
Speech, Language and Communication Problems in Young Children -- The Development of Communication : Speech and Language Acquisition -- Recognising Hearing Problems -- How to Recognise Speech, Language and Communication Problems -- Working with Parents -- Stammering and Early Dysfluency in Young Children -- Links between Social, Mental and Emotional Health Difficulties, and Communication Needs -- Autism Spectrum Disorders -- Language Programmes -- Supporting Young Children with Speech, Language and Communication Needs.
'A David Fulton book.'--Cover.
Revised edition of : How to manage communication problems in young children.
Includes bibliographical references and index.
Keywords: Speech disorders in children; Speech therapy for children; Language disorders in children